QSAR, Molecular Docking, and Molecular Dynamic of Novel Coumarin Derivatives as α-Glucosidase Inhibitor - Mutista Hafshah; Irvan Maulana Firdaus; Ika Nur Fitriani; Lutfiah Rahmawati (Jurnal Kimia Sains dan Aplikasi, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder posing a significant health risk. Effective treatments are continually sought. Coumarin derivatives with oxime ester groups have shown potential as antidiabetic agents by inhibiting the α-glucosidase enzyme, a key player in glycoprotein metabolism and postprandial hyperglycemia control. This makes lysosomal α-glucosidase a promising therapeutic target. A study used 28 coumarin derivatives with known α-glucosidase inhibitory IC50 values for computer-assisted drug design (CADD) through quantitative structure-activity relationship (QSAR) analysis, yielding a statistically robust equation for guiding new compound development. Subsequently, eleven new coumarin derivatives with oxime ester groups were synthesized, showing enhanced α-glucosidase inhibitory activity compared to the initial set. Molecular docking assays indicated that compounds 32, 37, 38, and 39 had lower free energy values than the native ligand, suggesting higher stability in target protein interactions. Notably, compound 38 had the lowest free energy (-8.351) and demonstrated lower root mean square deviation (RMSD) and root mean square fluctuation (RMSF) than the original ligand, indicating greater stability. The QSAR equation derived is:Log IC50 = 2.886 - 0.054 (LUMO) + 0.073 (μ) – 0.148 (α) – 0.046 (RD) + 0.046 (BM) + 0.001 (Vvdw) – 0.421 (qC2) + 1.138 (qC8) – 0.092 (qC9) + 2.61 (qC10) + 1.354 (qN1) (Eq 1) n=28; R=0.918; R2=0.843; SD=0.196; F hit/F tab=3.169; Sig =<0.01; PRESS = 1.376.Compound 38’s SMILES notation is:C\C(=N/OC(=O)\C=C/C1=CC=C(Br)C=C1)C1=CC2=CC(O)=C(CC(O)=O)C=C2OC1=O).